(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rehabilitation measures are an incentive to deter criminals from increasing misconduct by therapy or training. Bald acknowledged that rehabilitation is a criminal reduction technique, focused on the premise that neighborhood prisoners will improve and lead crime-free lives. Although other prevention initiatives aim to discourage children from participating in crime and delinquency until they do so, diversion services support adolescents who have previously involved in illegal or abusive behavior. Rehabilitation is also known as prevention of tertiary criminality. Recovery services may be administered inside or as part of any correctional justice punishment, such as parole or probation, although this is not a rehabilitation service prerequisite. Treatment and rehabilitation have been central to the development of criminal justice policy, and have played a significant role in criminology development. Punishment and revenge in recent years have drawn further publicity than recovery, but belief in care and healing has resurged with indications that some things are doing ’work,’ and a focus on policy making based on ’evidence.’ The role of Probationer Officer plays a vital role in this process of rehabilitation and treatment of offenders as he is one who has initiated the process at first stage. The system can be strengthened if he does his job fairly and honestly to lower the number of offenders in the future.